Pleistocene climate variability in eastern Africa influenced hominin evolution - Foerster, V; Asrat, A; Bronk Ramsey, C; Brown, ET; Chapot, MS; Deino, A; Duesing, W; Grove, M; Hahn, A; Junginger, A; Kaboth-Bahr, S; Lane, CS; et al. (Springer Nature, 2022)
Despite more than half a century of hominin fossil discoveries in eastern Africa, the regional environmental context of hominin evolution and dispersal is not well established due to the lack of continuous palaeoenvironmental records from one of the proven habitats of early human populations, particularly for the Pleistocene epoch. Here we present a 620,000-year environmental record from Chew Bahir, southern Ethiopia, which is proximal to key fossil sites. Our record documents the potential influence of different episodes of climatic variability on hominin biological and cultural transformation. The appearance of high anatomical diversity in hominin groups coincides with long-lasting and relatively stable humid conditions from ~620,000 to 275,000 years BP (episodes 1–6), interrupted by several abrupt and extreme hydroclimate perturbations. A pattern of pronounced climatic cyclicity transformed habitats during episodes 7–9 (~275,000–60,000 years BP), a crucial phase encompassing the gradual transition from Acheulean to Middle Stone Age technologies, the emergence of Homo sapiens in eastern Africa and key human social and cultural innovations. Those accumulative innovations plus the alignment of humid pulses between northeastern Africa and the eastern Mediterranean during high-frequency climate oscillations of episodes 10–12 (~60,000–10,000 years BP) could have facilitated the global dispersal of H. sapiens.